DIALOGUE AS A MEANS OF CREATIVE PERSONALITY DEVELOPMENT IN THE PROCESS OF STUDYING BIOCHEMISTRY (Pedagogy of Higher and Secondary Education, 2010)
The article considers some peculiarities of the dialogue as a way of the development of the creative personality in the course of biochemistry studying.
Keywords: creative personality; cognitive activity; dialogue; dialogue training